Try Another Version of This Question

Determine the equation of the vertical asymptote and the equation of the slant asymptote of the rational function.

`f(x) = (-6x^2+23x-11)/(2x-7)`

The equation of the vertical asymptote is

The equation of the slant asymptote is

Get help:

Box 1: Enter your answer as an equation. Example: y=3x^2+1, 2+x+y=3

Be sure your variables match those in the question

`x = 7/2`

Box 2: Enter your answer as an equation. Example: y=3x^2+1, 2+x+y=3

Be sure your variables match those in the question

`y = -3x+1`